FACTORS INFLUENCING PATIENTS’ REVISIT INTENTION TO PUBLIC HEALTH CENTER DURING COVID-19 PANDEMIC - Vera Valentine Saputri; Margaretha Pink Berlianto (Universitas Airlangga, 2023)
Background: COVID-19 was declared a community health emergency, prompting the Indonesian government to implement a large-scale social restriction policy on March 2022. As a result, the number of patient visits to the Public Health Center (PHC) decreased. Aims: This study aimed to analyze the factors affecting the revisit intention of patients at PHC during the COVID-19 pandemic. Methods: This observational study was conducted at PHC XYZ in West Jakarta in September and October 2022 using a cross-sectional approach. Inclusion and exclusion criteria were employed to select 244 samples. The data collected through a questionnaire with 37 questions were analyzed using PLS-SEM. Results: Government trust and trust in healthcare facilities positively affect revisit intention, with t-statistics of 4.816 and 0.003 as well as a p-value of 0.000. Meanwhile, perceived crowding and health risk, reputation, self-confidence, familiarity, and brand image did not significantly influence revisit intention at the PHC during the COVID-19 pandemic. Conclusion: This study showed that trust in government and healthcare facilities affects the revisit intention of patients. Patients trust that the Government can overcome COVID-19 and that PHC can be trusted during COVID-19 has a positive influence on patients' intention to revisit. It is important to identify the factors influencing revisit intention at PHC during the pandemic because PHC has a role as a primary healthcare service. Keywords: COVID-19, government trust, Public Health Center, revisit Intention, trust